PEMANFAATAN QUICK RESPONSE CODE UNTUK PENCARIAN INFORMASI PRODUK BERBASIS MOBILE - Budi Wasito (Jurnal Informatika dan Bisnis, 2020)
Dunlopillo's sales require higher mobility. When Sales is outside the store area, sales alsoexperience difficulties such as updating price information, and searching for productinformation. With the increase in the number of products, sales will be difficult to rememberinformation from products.QR Code is the development of a barcode or bar code that is only able to store informationhorizontally while the QR Code is able to store more information, both horizontally andvertically. The purpose of the QR Code is to convey information quickly and also getresponses quickly.Researchers collect data through indirect observation, interviews, and literature studies toexamine solutions that can be proposed and answer problems from the background ofresearch.Based on the research, an application is needed with the use of the QR Code to supportconvenience and convenience in carrying out Sales work activities. QR Code can help Salesin getting information more quickly.The conclusion obtained by the researcher is that the QR Code is needed by Sales tofacilitate Sales in conducting product searches, with the existence of mobile-basedapplications to make it easier for Sales to do marketing, mobile-based applications also helpretailers in making orders.Keywords: QR Code, Information, Mobile